Where the infection is isolated rather than the specific species correlates with adherence strength, whereas biofilm density remains static in clinically isolated Candida and arthroconidial yeasts - Mei ElGindi (23276131) (2021)
To colonize and infect the host, arthroconidial yeasts must avoid being killed by the host’s defenses. The formation of biofilms on implanted devices allows fungi to avoid host responses and to disseminate into the host. To better study the mechanisms of infection by arthroconidial yeasts, adherence and biofilm formation were assayed using patient samples collected over 10 years. In clinical samples, adherence varies within species, but the relative adherence is constant for those samples isolated from the same infection site. Herein we document, for the first time, in-vitro biofilm formation by Trichosporon dohaense, T. ovoides, T. japonicum, T. coremiiforme, Cutaneotrichosporon mucoides, Cutaneotrichosporon cutaneum, Galactomyces candidus, and Magnusiomyces capitatus on clinically relevant catheter material. Analysis of biofilm biomass assays indicated that biofilm mass changes less than 2-fold, regardless of the species. Our results support the hypothesis that most pathogenic fungi can form biofilms, and that biofilm formation is a source of systemic infections. Other Information Published in: Canadian Journal of Microbiology License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1139/cjm-2020-0215